CAN AUDITOR INDUSTRY EXPERTISE REDUCE INCIDENCES OF MISREPORTING? - Patin, Jeanne Claire; Jens, William G. (International Journal of Accounting & Finance Review, 2022)
The purpose of this paper is to examine the influence of auditor industry expertise on the relationship between equity incentives and financial misreporting. Previous studies report mixed findings on the relationship between financial misreporting and equity incentives; however, they fail to consider detection mechanisms such as auditor industry expertise. Auditor industry experts have been shown to have better financial reporting quality. This study evaluates the interaction of auditor industry expertise (“specialists”) on the relationship between equity incentives as proxied through vega and financial misreporting such as abnormal accruals, likelihood of just meeting or beating analysts’ earnings forecasts, and financial restatements. Vega measures the sensitivity of the CEO’s portfolio to a .01 change in stock volatility. Results indicate that there does not appear to be statistically significant evidence of a relationship between equity incentives and financial misreporting in firms that are audited by an auditor industry expert. This conclusion provides important information to those concerned with the possibility that senior executives whose compensation are largely tied to performance measures are potentially incented to misreport financial results. While this data may seem counter-intuitive, we conclude that firms do not benefit from auditor industry expertise as it relates to equity incentives and financial misreporting. JEL Classification Codes: M12, M41, M42.